Conjugate laminar natural convection and surface radiation in enclosures: Effects of protrusion shape and position. (August 2016) - Patil, Swapnil; Sharma, Anil Kumar; Velusamy, K.
Abstract: A 2-D numerical analysis has been carried out for conjugate heat transfer of laminar natural convection and surface radiation in square enclosure with broad protrusions. The air filled vertical enclosure has two horizontal adiabatic walls and two differentially heated isothermal walls. Investigations are carried out for Rayleigh number in the range of 10 3 to 10 6 and surface emissivity values 0 to 1. Protrusions of different shapes and at different positions are considered in this study. The governing equations of fluid flow and heat transfer with surface radiation are solved using finite volume method and SIMPLE algorithm. The convective and radiative Nusselt numbers are plotted against different key parameters. It has been observed that protrusion affects significantly the overall heat transfer and also modifies the temperature and flow fields in the enclosure. Surface radiation interaction leads to formation of secondary cell between the cold isothermal wall and protrusion. The intensity of vortex decreases gradually as protrusion moves from the hot wall to cold isothermal wall.